Cultura gastronómica y los emprendimientos turísticos en la Parroquia Patricia Pilar, año 2019 - Estrella Briones, Dallan Yaritza (2019)
In the present research topic GASTRONOMIC CULTURE AND ITS INCIDENCE IN TOURISM ENTREPRENEURSHIPS AT PATRICIA PILAR PARISH, 2019. Its purpose is to promote the culinary culture of the Patricia Pilar parish, with the purpose of generating tourist ventures through it in the zone. With the promotion of gastronomic culture, the aim is to boost tourism and innovate "gastronomic tourism". This research is detailed in the following chapters. Chapter I: The main idea of the research to be developed is detailed in conjunction with its general objective and its specific objectives which are the guidelines for the project to be developed. Chapter II: This chapter focuses on the criteria of several national and international authors, bibliographic references of gastronomy, tourism and entrepreneurship (Theoretical Framework) which are taken into account for the progress of the project, improving the reader's understanding, Continuing with the background of the investigation allowing the researcher to establish his theoretical position on the hypothesis. Chapter III: This part of the chapter includes the acquisition of data by means of research instruments based on hypotheses as well as statistical graphs that demonstrate the knowledge of the respondents about the research topic, facilitating understanding about the project and finally the general and specific conclusions and recommendations. Chapter IV: In this last stage of the project, the proposal is implemented to improve the development of tourism entrepreneurship and the promotion of culinary culture through the creation of pages on social networks and a digital brochure.